Effect of combined aerobic and resistance training in body composition of obese postmenopausal women - Fabrício E. Rossi; Camila Buonani; Juliana Viezel; Eduardo P. da Silva; Tiego A. Diniz; Vanessa R. dos Santos; Rômulo A. Fernandes; Ismael F. Freitas Junior (Universidade Estadual Paulista (UNESP), 2015)
The aim of this study was to investigate the effects of a 16-week program of combined aerobic and resistance training on the body composition of postmenopausal women who are obese. The participants were divided into two groups: training group (TG, n = 37) and non-trained control group (CG, n = 18). The trunk fat, fat mass, percentage of fat mass and fat-free mass were estimated using DXA. Three nonconsecutive 24-hour dietary recalls were conducted. The training protocol consisted of 50 minutes of resistance training followed by 30 minutes of aerobic training. After the 16-week training program, differences were observed in trunk fat (CG= 0.064 x TG= -0.571 Kg; p-value = .020), fat mass (CG= -0.088 x TG= -1.037 Kg; p-value = .020) and fat-free mass (CG= -0.388 x TG= 1.049 Kg; p = .001). Therefore, a 16-week program of systematic combined aerobic and resistance training in obese postmenopausal women was effective in improving fat-free mass and decreasing both whole and abdominal adiposity.